2017
DOI: 10.1002/nml.21282
|View full text |Cite
|
Sign up to set email alerts
|

Do operating reserves stabilize spending by nonprofit organizations?

Abstract: The public budgeting literature has a long and rich tradition that examines the role of budget stabilization funds as fiscal stabilizers for state and local governments during periods of declining revenues and deteriorating economic conditions. Similarly, nonprofit organizations may accumulate operating reserves that allow them to smooth out annual imbalances between revenues and expenses, especially when facing a fiscal shock. Agency theory, on the other hand, indicates that managers might use these reserves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
15
1
4
Order By: Relevance
“…Statistical inference with DEA scores computed from nonprofit tax data should consider the smaller sample when making theoretical efficiency claims. Example of design approaches with solutions for the nonprofit size sampling constraint can be seen in Calabrese () and Searing ().…”
Section: Resultsmentioning
confidence: 99%
“…Statistical inference with DEA scores computed from nonprofit tax data should consider the smaller sample when making theoretical efficiency claims. Example of design approaches with solutions for the nonprofit size sampling constraint can be seen in Calabrese () and Searing ().…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a measurement of operational activity is revenue such as fees for services or the sale of goods, which is reported as “Program service revenue” on Form 990 Part I line 9, again excluding any negative values (Searing, ). For the following analysis, an organization's subsector is defined by the first letter of the National Taxonomy of Exempt Entities (NTEE) Classification System as developed by the National Center for Charitable Statistics assigned to its employer identification number (see similar usage of NTEE codes in, e.g., Calabrese, ).…”
Section: Data and Resultsmentioning
confidence: 99%
“…In corporate finance, “cash holdings” refer to cash‐on‐hand and savings, including temporary or short‐term investments that can easily be converted to cash. Previous research in nonprofit finance has defined the term similarly: “cash holdings” are cash, savings, and temporary cash investments held by nonprofit organizations (Calabrese, ; Core et al, ; Fisman & Hubbard, ; Ramirez, ).…”
Section: Nonprofit Cash Holdingsmentioning
confidence: 99%
“…Organizations also accumulate cash to use as a buffer against revenue shortfalls and may seek growth opportunities by increasing program expenses to provide more goods and services (Core et al, ). Studies have also suggested the presence of agency problems as an alternative explanation for organizations' cash holdings (Jensen, ); however, some studies have rejected this idea (e.g., Calabrese, ). Unlike debt and equity that entail formal monitoring by external constituencies, cash gives discretion to managers so that they can expropriate cash for private gain (Ramirez, ).…”
Section: Nonprofit Cash Holdingsmentioning
confidence: 99%
See 1 more Smart Citation